2013
DOI: 10.1093/ejcts/ezt017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of complex coronary artery disease in patients with diabetes: 5-year results comparing outcomes of bypass surgery and percutaneous coronary intervention in the SYNTAX trial†

Abstract: In both diabetic and non-diabetic patients, PCI resulted in higher rates of MACCE and repeat revascularization at 5 years. Although PCI is a potential treatment option in patients with less-complex lesions, CABG should be the revascularization option of choice for patients with more-complex anatomic disease, especially with concurrent diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
211
1
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(240 citation statements)
references
References 23 publications
7
211
1
21
Order By: Relevance
“…It was concluded that, although PCI is a potential treatment option in patients with less complex lesions CABG should be the revascularization choice for DM patients with complex anatomic disease. 245 Data obtained in recent registries support a better outcome for DM treated with CABG, compared with DES even in terms of mortality, at the expense of a higher stroke rate with CABG. 246 In an analysis of 86,244 patients ≥65 years of age undergoing CABG and 103,549 patients undergoing PCI from 2004 to 2008, four-year survival was significantly higher with surgery and the association of surgery with improved survival was most marked in insulintreated DM.…”
Section: Type Of Intervention: Coronary Bypass Graft Vs Percutaneousmentioning
confidence: 88%
“…It was concluded that, although PCI is a potential treatment option in patients with less complex lesions CABG should be the revascularization choice for DM patients with complex anatomic disease. 245 Data obtained in recent registries support a better outcome for DM treated with CABG, compared with DES even in terms of mortality, at the expense of a higher stroke rate with CABG. 246 In an analysis of 86,244 patients ≥65 years of age undergoing CABG and 103,549 patients undergoing PCI from 2004 to 2008, four-year survival was significantly higher with surgery and the association of surgery with improved survival was most marked in insulintreated DM.…”
Section: Type Of Intervention: Coronary Bypass Graft Vs Percutaneousmentioning
confidence: 88%
“…The advent of the DES era led to improved results among diabetics, thereby narrowing the outcome gap with surgical revascularization [34,35]. However, recent randomized, controlled trials, such as the Coronary Artery Revascularization in Diabetes (CARDia) trial, the Synergy between PCI with Taxus and cardiac surgery (SYNTAX) trial, and the Future Revascularization Evaluation in patients with Diabetes Mellitus (FREEDOM) trial, did demonstrate long-term superiority of coronary bypass over PCI, mainly driven by a lower TLR rate, particularly in patients with highly complex lesions [36][37][38]. One major limitation of any randomized controlled trial comparing surgery with PCI is the presence of multiple exclusion criteria that reduces the external validity of trial-related findings.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-specified DM-subgroup analysis (n=452) of SYNTAX (SYNergy Between PCI With TAXus and Cardiac Surgery) 84 showed that the 5-year composite MACCE rate was significantly higher in patients with DM after PCI compared with CABG (PCI: 46.5% vs CABG: 29.0%; P< 0.001) mainly due to an increased risk of repeat revascularization (PCI: 35.3% vs CABG: 14.6%; P< 0.001). 85 However, the difference between PCI and CABG is larger for patients with DM than for those without.…”
Section: Cabg Versus Pci In Multivessel Cadmentioning
confidence: 99%